Unusually Warm Summer Temperatures Exacerbate Population and Plant Level Response of Posidonia oceanica to Anthropogenic Nutrient Stress - Helber, Stephanie B.; Procaccini, Gabriele; Belshe, E. Fay; Santillan-Sarmiento, Alex; Cardini, Ulisse; Bröhl, Stefanie; Schmid, Michael; Reuter, Hauke; Teichberg, Mirta (Frontiers in Plant Science, 2021)
Posidonia oceanica is a key foundation species in the Mediterranean providing valuable ecosystem services. However, this species is particularly vulnerable towards high coastal nutrient inputs and the rising frequency of intense summer heat waves, but their combined effect in situ has received little attention so far. Here, we investigated the effects of in situ nutrient addition during an unusually warm summer over a 4- month period, comparing different morphological, physiological and biochemical population metrics of seagrass meadows growing in protected areas (Ischia) with meadows already exposed to significant anthropogenic pressure (Baia - Gulf of Pozzuoli). Our study highlights that the effects of warmer than usual summer temperatures on the population level of seagrass meadows can be exacerbated if the plants are already exposed to higher anthropogenic pressures. Morphological and population level indicators mainly changed over time, possibly impacted by season and the warmer temperatures, and displayed more pronounced reductions in seagrasses from impacted sites. The additional nutrient supply had even more deleterious effects, as shown by a decrease in approximately 67 % in cover in fertilized plots at high impacted sites and 33 % at low impacted sites. Moreover, while rhizome starch concentration showed a seasonal increase in plants from low impacted sites it displayed a trend of a 27% decrease in fertilized plots of the high impacted sites. Epiphyte biomass was approximately four- fold higher on leaves of plants growing in impacted sites and even doubled with the additional nutrient input. Predicting and anticipating stress in P. oceanica is of crucial importance for conservation and management efforts, given the limited colonizing and reproductive ability and extremely slow growth of this ecosystem engineer. Our results suggest that monitoring efforts should focus especially on leaf area index (LAI), carbohydrate concentrations in the rhizomes, and epiphyte cover on leaves as indicators of the onset of stress in Posidonia oceanica, which can be used by decision makers to take appropriate measures in order to identify warning indicators of seagrass stress before damage to the ecosystem becomes irreversible, minimize future human interference and strengthen the resilience of these important ecosystems.